Cholinergic dysfunction contributes to gait disturbance in early Parkinson's disease - Rochester, L.; Yarnall, A. J.; Baker, M. R.; David, R. V.; Lord, S.; Galna, B.; Burn, D. J. (Brain (London, England : 1878), 2012)
Gait disturbance is an early feature in Parkinson's disease. Its pathophysiology is poorly understood; however, cholinergic dysfunction may be a non-dopaminergic contributor to gait. Short-latency afferent inhibition is a surrogate measure of cholinergic activity, allowing the contribution of cholinergic dysfunction to gait to be evaluated. We hypothesized that short-latency afferent inhibition would be an independent predictor of gait dysfunction in early Parkinson's disease. Twenty-two participants with Parkinson's disease and 22 age-matched control subjects took part in the study. Gait was measured objectively using an instrumented walkway (GAITRite), and subjects were asked to walk at their preferred speed for 2 min around a 25-m circuit. Spatiotemporal characteristics (speed, stride length, stride time and step width) and gait dynamics (variability described as the within subject standard deviation of: speed, stride time, stride length and step width) were determined. Short-latency afferent inhibition was measured by conditioning motor evoked potentials, elicited by transcranial magnetic stimulation of the motor cortex, with electrical stimuli delivered to the contralateral median nerve at intervals ranging from N20 (predetermined) to N20 + 4 ms. Short-latency afferent inhibition was determined as the percentage difference between test and conditioned response for all intervals and was described as the group mean. Participants were optimally medicated at the time of testing. Participants with Parkinson's disease had significantly reduced gait speed (P = 0.002), stride length (P = 0.008) and stride time standard deviation (P = 0.001). Short-latency afferent inhibition was also significantly reduced in participants with Parkinson's disease (P = 0.004). In participants with Parkinson's disease, but not control subjects, significant associations were found between gait speed, short-latency afferent inhibition, age and postural instability and gait disorder score (Movement Disorders Society Unified Parkinson's Disease Rating Scale) and attention, whereas global cognition and depression were marginally significant. No other gait variables were associated with short-latency afferent inhibition. A multiple hierarchical regression model explored the contribution of short-latency afferent inhibition to gait speed, controlling for age, posture and gait symptoms (Postural Instability and Gait Disorder score-Movement Disorders Society Unified Parkinson's Disease Rating Scale), attention and depression. Regression analysis in participants with Parkinson's disease showed that reduced short-latency afferent inhibition was an independent predictor of slower gait speed, explaining 37% of variability. The final model explained 72% of variability in gait speed with only short-latency afferent inhibition and attention emerging as independent determinants. The results suggest that cholinergic dysfunction may be an important and early contributor to gait dysfunction in Parkinson's disease. The findings also point to the contribution of non-motor mechanisms to gait dysfunction. Our study provides new insights into underlying mechanisms of non-dopaminergic gait dysfunction, and may help to direct future therapeutic approaches.